Psychological Training in Kurash Wrestling - Menglimurod ougli, Amandavlatov Toshmamat (European Journal of Life Safety and Stability (2660-9630), 2022)
This article analyzes the importance of psychological preparation for participation in competitions, the need to use psychodiagnostics for obtaining data that would allow predicting future achievements and circumventing obstacles to achieving the intended result.